Studying the interactions among Industry 5.0 and circular supply chain: Towards attaining sustainable development. (February 2023) - Dwivedi, Ashish; Agrawal, Dindayal; Jha, Ajay; Mathiyazhagan, K.
Highlights: Modeled 16 drivers of Industry 5.0 and Circular Supply Chain. The drivers are analyzed in sustainable development context. 'Management support and efficient workforce for I5.0 transformation' has attained the highest driving power. Several insights and managerial implications are specified for I5.0 and CSC transformations. Abstract: The circular supply chain (CSC) paradigm advocates a shift in business practices from linear to circular models for the planet's sustainability. CSC involves recovery processes that result in capturing additional value and reduction of carbon footprints in the supply chain. Industry 5.0 (I5.0) revolution involves a network of connected devices and systems across the supply chain to facilitate intelligent manufacturing as per customer-specific requirements. It can be an enabling tool for achieving sustainability via a circular economy. In the existing literature, there is an absence of a framework connecting the drivers of I5.0 and CSC. The present study identifies 16 potential drivers in the context of achieving I5.0 and CSC synergy from the literature review and in consultation with industry professionals and practitioners. To identify the criticality strength of drivers, a mixed model is constructed using the modified Total Interpretive Structure Model (m-TISM) and the Cross-Impact Matrix Multiplication Applied to Classification (MICMAC). The m-TISM arranges the binary interactions between the drivers, while MICMAC arranges the precise evaluations specific to the dependence and driving power of the drivers. The exercise results in a framework for handling efficiently the drivers of I5.0 and CSC to attain sustainable development. The results from the study reflect that 'Management support for CSC and I5.0 transformation' and 'Organization readiness and expectation in the transformation to CSC and I5.0′ are the drivers with maximum driving power and hence should be given high priority in designing the implementation plan. Also, the driving element 'Attitudinal transition of consumers towards CSC and I5.0 models' is among the top-level drivers in the analysis, indicating the importance of creating awareness and attitude building in realizing this business process change. In the current global business environment of high competition and sustainability pressure, the study provides guidelines to company directors and supply chain strategists in achieving efficiency and sustainability objectives via I5.0 and CSC approaches. The proposed framework could also assist the various government and industry associations in formulating policies for I5.0, CSC and sustainable development.